2017
DOI: 10.1111/head.13096
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Patients With Chronic Tension‐Type Headache: A Case‐Control Study

Abstract: Decreased serum 25(OHD) concentration was associated with CTTH. Intervention studies are required to find out if supplementation of vitamin D is effective in patients with CTTH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…Preliminary studies have found an association between vitamin deficiencies and headaches, but large studies on the topic are lacking. 22,23 When examining potential effect modification by gender, we did not observe a statistically significant difference between ORs for number of ACEs and headaches in females and males. The results from observational studies conducted in adults have shown gender differences in the association between headache and ACEs.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Preliminary studies have found an association between vitamin deficiencies and headaches, but large studies on the topic are lacking. 22,23 When examining potential effect modification by gender, we did not observe a statistically significant difference between ORs for number of ACEs and headaches in females and males. The results from observational studies conducted in adults have shown gender differences in the association between headache and ACEs.…”
Section: Discussionmentioning
confidence: 58%
“…For example, children lacking proper nutrition resulting from limited family financial resources may be at increased risk of headaches. Preliminary studies have found an association between vitamin deficiencies and headaches, but large studies on the topic are lacking …”
Section: Discussionmentioning
confidence: 99%
“…Another study also showed 100 patients with chronic TTH had a significantly higher prevalence of musculoskeletal pain, muscle tenderness and weakness, and bone tenderness score compared to controls [60]. In addition, they showed vitamin D insufficiency was accompanied by an increased risk of chronic TTH [60]. Similarly, Hanci et al found lower 25(OH)D levels in those with headache compared to controls, with not statistically significant difference [53].…”
Section: Vitamin D Deficiency and Tension-type Headachesmentioning
confidence: 95%
“…This muscles hypersensitivity together with and sensory hyperinnervation may exacerbate musculoskeletal pain [22]. Another study also showed 100 patients with chronic TTH had a significantly higher prevalence of musculoskeletal pain, muscle tenderness and weakness, and bone tenderness score compared to controls [60]. In addition, they showed vitamin D insufficiency was accompanied by an increased risk of chronic TTH [60].…”
Section: Vitamin D Deficiency and Tension-type Headachesmentioning
confidence: 99%
See 1 more Smart Citation